2020
DOI: 10.2478/sjph-2021-0004
|View full text |Cite
|
Sign up to set email alerts
|

Association between preventive behaviour and anxiety at the start of the COVID-19 pandemic in Slovenia

Abstract: IntroductionThe first large outbreak of SARS-CoV-2 in Europe occurred in Northern Italy in February 2020. The relatively fast spread of the infection to Slovenia was expected, and preventive measures for its suppression were widely discussed.MethodsAn online questionnaire was designed to evaluate adherence to preventive measures and the extent to which the taking of preventive measures was associated with people’s anxiety level, psychological burden, their perceived vulnerability to disease, germ aversion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 34 publications
4
28
1
2
Order By: Relevance
“…The self-assessed psychological burden was in fairly weak positive correlation with vaccination intention and advising vaccination, but the correlation between the anxiety score and all three preventive measure values was close to zero. These results differ from the findings in the general population at the initial stage of the pandemic, when a higher level of preventive behavior was found in individuals who experienced greater psychological distress, were more anxious, expressed greater perceived infectability, and experienced greater germ aversion [16]. There was even a negative correlation between the anxiety score and preventive behavior score in accordance with the recently published research performed by Wang et al [45] who investigated the association between the psychological impact of the COVID-19 outbreak and taking precautionary measures in China, and showed that greater adherence to preventive measures was linked to lower degrees of anxiety, stress and depression.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The self-assessed psychological burden was in fairly weak positive correlation with vaccination intention and advising vaccination, but the correlation between the anxiety score and all three preventive measure values was close to zero. These results differ from the findings in the general population at the initial stage of the pandemic, when a higher level of preventive behavior was found in individuals who experienced greater psychological distress, were more anxious, expressed greater perceived infectability, and experienced greater germ aversion [16]. There was even a negative correlation between the anxiety score and preventive behavior score in accordance with the recently published research performed by Wang et al [45] who investigated the association between the psychological impact of the COVID-19 outbreak and taking precautionary measures in China, and showed that greater adherence to preventive measures was linked to lower degrees of anxiety, stress and depression.…”
Section: Discussioncontrasting
confidence: 99%
“…Parts of the instrument were as follows: assessment of preventive behavior : respondents evaluated their level of agreement with 10 statements describing different preventive measures from 1 (absolutely not) to 5 (absolutely yes) as described previously [ 16 ] with the additional statement ‘I regularly take care for aeration of premises’. For further analysis the average value of all statements was calculated for each respondent to obtain the preventive behavior score (Cronbach’s alpha = 0.75).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations